Emotion Regulatory from Riding Aggressively on Motor Bike Students - Imam Dedikasi Malik Nur; Asniar Khumas; St. Hadjar Nurul Istiqamah (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Aggressive driving is aggressive behaviour carried out by drivers that can harm other drivers and themselves. Aggressive driving can be a contributing factor to increased accidents and traffic violations. One factor that can influence aggressive driving is emotional regulation. The study aimed to analyze the impact of emotional regulation on driving aggressiveness in motorcycle students. The study used an emotional regulation scale and a driving aggressiveness scale. Respondents in this study of male students in the city of Makassar were as many as 123, obtained using convenience sampling. This research uses a quantitative approach with nonparametric statistical data analysis techniques of ordinal regression methods. The results of this study show that there is a negative and significant influence of emotional regulation on driving aggression in male students in Makassar City (B = -0,063, p = 0,008), with 4.6% of driving aggressiveness contributing to the explanation of emotion regulation variance (R2 = 0,046). The higher the driver's ability to regulate emotions, the lower the motorcyclist's driving aggressiveness, and the worse the rider's emotion regulation ability, the higher the motorcycle rider's driving aggression. This research could be the basis for intervention or emotional regulation training in drivers in order to improve their ability to regulate emotions, thereby reducing levels of aggression while driving.